PENGEMBANGAN MEDIA PERMAINAN LUKER PADA MUATAN PEMBELAJARAN PPKN KELAS V SEKOLAH DASAR - Zulfa Ika Putri; Otib Satibi Hidayat; Dudung Amir Soleh (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This research and development produce to develop learning media in the form of the LUKER game (Ludo Keragaman) in PPKn content with socio-cultural diversity material for fifth grade elementary school students. The method used in this research is research and development (R&D) is ADDIE model. This study involved one media expert, one material expert, one linguist, three students on fifth grade at SDN Tugu Utara 17 for one to one trial, and twelve students on fifth grade at SDN Tugu Utara 17 for small group trial. Data collection techniques used in the development of this ludo game are interviews, observations, and questionnaires. The results of this ludo game media trial obtained a score of 85% from media experts, 92.5% from material experts, and 87.5% from linguists. The results of the one-to-one user trial got an average score of 100%, while the small group trial got an average score of 100%. This shows that the LUKER game media obtained a very good score, so that it was declared worthy of being used as a learning media for PPKn theme 8 (Lingkungan Sahabat Kita) for fifth grade elementary school.